FACTORS INFLUENCING PURCHASE INTENTION TOWARD ONLINE FOOD DELIVERY SERVICE: A CASE STUDY OF EXPERIENCED CONSUMERS IN HUNAN PROVINCE, CHINA - Zhu, Lu; Li, Changhan; Phongsatha, Satha (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The purpose of this research was to identify the factor influence online food delivery service purchasing intention who live in Hunan province, China. The variables that had been used in this study framework were Price value, Health consciousness, Food safety concern, Prestige value, Affordances value and Visibility. The questionnaire was conducted and selected from 200 respondents in Hunan province by using the non-probability sampling method as purposive sampling. The Multiple Linear Regression was applied for hypothesis testing. The result revealed that Food Safety Concern (β = 0.31, p=.02). was the most influence factor toward consumers’ purchasing intention of online food delivery service. Thus, it showed that Food Safety Concern towards online food delivery service was the most important in determining online food delivery service of Hunan province consumers. The finding suggested that by enhancing the consumer purchasing intentions, the online food delivery service owners should rather focus on Food Safety Concern factor.